Four novel variants identified in the ACADVL gene causing very-long-chain acyl-coenzyme A dehydrogenase deficiency in four unrelated Chinese families - Li, Lulu; Tang, Yue; Zhao, Jinqi; Gong, Lifei; Yang, Nan; Wang, Shunan; Yang, Haihe; Kong, Yuanyuan (Frontiers in Genetics, 2024)
Background: This article reports and discusses the biochemical and genetic characteristics of four very-long-chain acyl-CoA dehydrogenase deficiency (VLCADD) patients, clarifying their pathogenic genetic factors and evaluating the application value of genetic diagnosis in the early diagnosis of VLCADD. Methods: Patients underwent blood tandem mass spectrometry (MS/MS), urine gas chromatography (GC/MS), and high-throughput sequencing technology. New variants were analyzed for pathogenicity using bioinformatics software. Using Swiss PDB Viewer software to predict the effect of variant on the structure of very-long-chain acyl-CoA dehydrogenase (VLCAD)protein. Result: A total of four VLCADD patients were diagnosed. They revealed elevated levels of C14, C14:1, C14:2, C14:1/C2, C14:1/C10, and C14:1/C12:1. Two patients were early-onset neonatal cases and died during infancy and neonatal period,respectively. Seven kinds of variants were detected, including four novel variants. The bioinformatics software revealed that the variants were harmful, and the Swiss PDB Viewer results suggest that variation affects protein conformation. Conclusions: This study identified four novel ACADVL gene variants. These findings contribute to the understanding of the genetic basis and pathogenesis of VLCADD. Meanwhile, the study enriches the genetic mutation spectrum and the correlation between genotypes and phenotypes of VLCADD, indicating that genetic diagnosis plays an essential role in the early diagnosis and treatment of VLCADD.